Development of clinical practice guidelines for dentists: methods for topic selection - van der Sanden WJM, Mettes DG, Grol RPTM, Plasschaert AJM, Verdonschot EH. (Blackwell Synergy, 2002)
The aim of this study was to compare four methods for assessing the preferences of the dental profession for topics to be considered for the development of clinical practice guidelines.